2023
DOI: 10.3390/polym15071678
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varying Curing Conditions on the Strength of Biopolymer Modified Sand

Abstract: Recently, the improvement of the engineering properties of soil has been centered on using sustainable and eco-friendly materials. This study investigates the efficacy of three biopolymers: Acacia, sodium alginate, and pectin, on the unconfined compressive strength (UCS) of dune sand. The UCS test measured the effects of the biopolymer type and concentration, curing intervals and temperature, and moisture loss. The changes in the morphology caused by the biopolymer addition were examined via scanning electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…By comparing 1 PV and 0.75 PV, it was found that in the case of AG, 0.75 PV was almost twice as strong as 1PV. In the case of SA and P, the values increased with increasing percentage of biopolymer (Lemboye & Almajed, 2023).…”
Section: Effect Of Different Biopolymer Percentages On Ucs With Diffe...mentioning
confidence: 93%
“…By comparing 1 PV and 0.75 PV, it was found that in the case of AG, 0.75 PV was almost twice as strong as 1PV. In the case of SA and P, the values increased with increasing percentage of biopolymer (Lemboye & Almajed, 2023).…”
Section: Effect Of Different Biopolymer Percentages On Ucs With Diffe...mentioning
confidence: 93%
“…Curing age is an important factor affecting the strength of improved soils [42]. The curing age generally ranges from 0 to 60 days, and the curing time plays a key role in improving the strength and deformation resistance of the improved soil [55]. In this period, the differences of various improved soils are relatively significant, and there is an optimal curing age.…”
Section: Effects Of Curing Age On the Mechanical Properties Of Biopol...mentioning
confidence: 99%
“…The linear relationships of E50-UCS and UCS-TS were obtained, which are closely related to temperature. Lemboye et al [55] studied the effects of sodium alginate and pectin on the unconfined compressive strength (UCS) of sand. The UCS test measured the effects of the biopolymer type and concentration, curing interval and temperature, and water loss.…”
Section: Effects Of Temperature Changes On the Strength Of Biopolymer...mentioning
confidence: 99%
“…The addition of lignin to CL soil resulted in a reduction in the effective angle of shearing resistance and an enhancement of effective cohesion by 22.1% and 120.8% [ 6 ]. Lemboye and Almajed [ 7 ] improved the UCS of pectin-stabilized sandy soil by 137-fold and attributed the strength gain to the loss in the moisture of the stabilized sand. Hamza et al [ 8 ] evaluated the long-term strengthening effect of a problematic swelling clay on treatment with guar gum biopolymer and noted a linear increase in strength with the curing period, with the UCS attaining 654 kN/m 2 after 365 days.…”
Section: Introductionmentioning
confidence: 99%